Effectiveness of Health Educational Program on Nurses’ Knowledge About Communication Skills with Children at Welfare Children Teaching Hospital in Baghdad City - ali, ammar; Al-mosawi, Khatam (Iraqi National Journal of Nursing Specialties, 2019)
Background: Therapeutic communication is the basis of interactive relationships among nursing team and their children: that affords opportunities to establish rapport, understand the client’s experience, formulate individualized or client interventions and optimize health care resources. Objectives: The main aim of the study is to determine the Effectiveness of Education Program on Nurses’ Knowledge about Communication Skills with Children. Methodology: A quasi-experimental study was conducted in Children Welfare Teaching Hospitals from 7th, October 2018 to the 20th, May 2019. The program and instruments have been constructed by the researcher for the purpose of the study. A non- probability purposive sample of (39) nurses who work in Children Welfare Teaching hospitals were into study group consisted of (30) nurses who were exposed to an education program. The study instrument is composed of two parts: first part deals with the socio- demographic characteristics of the nurses, while the second part deals with the Knowledge test which consists of (35) items (multiple choices) questionnaires divided into (5) main dimensions related to nurse’s knowledge about communication skills with children. Validity of the study instrument is determined through a panel of experts and reliability of the instrument was determined through (test – retest) method. The analysis of the data used is descriptive statistics and statistical inferential, in order to find the differences among the pre-test, post-test1 and post-test 2 in study group. Results: The study findings indicate that there are highly significant differences between (pre and post-test1 and post-test2) in the study group regarding (nurse’s knowledge about communication skills with children. Recommendations: The researcher recommended specific training courses for nurses with exam to get the benefit and to have effect on the pediatric nurses knowledge, and pediatric nurses must have a continuous courses about communication skills with children.